2014 IEEE International Conference on Image Processing (ICIP) 2014
DOI: 10.1109/icip.2014.7025817
|View full text |Cite
|
Sign up to set email alerts
|

Lossless coding of hyperspectral images with principal polynomial analysis

Abstract: The transform in image coding aims to remove redundancy among data coefficients so that they can be independently coded, and to capture most of the image information in few coefficients. While the second goal ensures that discarding coefficients will not lead to large errors, the first goal ensures that simple (point-wise) coding schemes can be applied to the retained coefficients with optimal results. Principal Component Analysis (PCA) provides the best independence and data compaction for Gaussian sources. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In [46] we explored lossless hyperspectral image coding using curvilinear techniques (family iii) based on Principal Polynomial Analysis (PPA) [33]. PPA exploits regression to remove non-linear dependencies that remain after linear feature extraction (e.g., after classical PCA).…”
mentioning
confidence: 99%
“…In [46] we explored lossless hyperspectral image coding using curvilinear techniques (family iii) based on Principal Polynomial Analysis (PPA) [33]. PPA exploits regression to remove non-linear dependencies that remain after linear feature extraction (e.g., after classical PCA).…”
mentioning
confidence: 99%
“…In [14] we explored lossless hyperspectral image coding using curvilinear techniques based on Principal Polynomial Analysis (PPA) [13]. In that work, it was shown that PPA achieves higher energy compaction and statistical independence than PCA.…”
Section: Introductionmentioning
confidence: 99%